Wanted Workers but Unwanted Mothers: Mobilizing Moral Claims on Migrant Care Workers' Families in Israel. (13th July 2016) - Kemp, Adriana; Kfir, Nelly
Abstract : Literature on global care work deals with biopolitical tensions between care markets and exclusionary migration regimes leading to the formation of transnational families. Nevertheless, it disregards how these tensions produce "illegal" families within countries of destination, catalyzing the mobilization of moral claims over their recognition in the local civil society. To fill this lacuna, this article looks at the interface between migration policies controlling the reproductive lives of migrant care workers and the mobilization of ethical claims and moral constructions of care from below (i.e., movements and organizations advocating for care workers). Based on fieldwork in Israeli advocacy NGOs and the 2009 anti-deportation campaign, we suggest that the sociolegal position of migrant care workers' families in destination countries is shaped not only by state policies and market dynamics but also by the types of social mobilizations, ethical evaluations, and pragmatic strategizing they spur in civil society. Findings show that while anti-deportation networks and NGO's advocacy succeeded in achieving public recognition of the reproductive needs and lives of care workers, their forms of moral reasoning and strategizing reinforced definitions of care workers as primarily workers and of their children as humanitarian exceptions to the non-immigration regime. We conclude by arguing that the transformative power of the politics of ethical claims from below in stringent ethnonational regimes like the Israeli may be contingent on its not disrupting the tensions between wanted workers and unwanted families but rendering them manageable. As such, civil society's social and moral agency broadens the range of actors and dynamics shaping the globalization of care as well as its contradictions. La literatura del trabajo de cuidado global trata con tensiones biopolíticas entre los mercados de atención y los regímenes de migración elitista lo cual conducen a la formación de las familias transnacionales. Sin embargo, no se tiene en cuenta cómo estas tensiones producen familias "ilegales" dentro de los países de destino, catalizando la movilización de demandas morales sobre su reconocimiento en la sociedad civil local. Para llenar esta laguna, el artículo analiza la interrelación entre las políticas de migración que controlan la vida reproductiva de los trabajadores de cuidado y la movilización de la demanda ética y construcciones morales de atención desde abajo. Basado en el trabajo de campo en las ONG de defensa israelíes y la campaña anti-deportación de 2009 se sugiere que la posición socio-legal de las familias de cuidadores migrantes en los países de destino están conformados no sólo por las políticas estatales y la dinámica del mercado, sino también por el tipo de movilizaciones sociales, evaluaciones éticas y la estrategia pragmática que incitan en la sociedad civil. Los resultados muestran que mientras que las redes anti-deportación y la defensa de las ONG tuvieron éxito en lograr el reconocimiento público sobre las necesidades reproductivas y las vidas de los trabajadores de cuidado, sus formas de razonamiento moral y estratégicamente reforzaron definiciones de trabajadores de cuidado principalmente como trabajadores y sus hijos como excepciones humanitarias al régimen de no-inmigración. Se concluye argumentando que el poder transformador de la política de alegaciones éticas desde abajo en regímenes étnico-nacionales como el israelí puede ser contingente a la no interrupción de las tensiones entre los trabajadores deseados y familias no deseadas pero representándolas manejable. Como tal, la agencia social y moral de la sociedad civil amplía la gama de actores y dinámicas que dan forma a la globalización del cuidado así como a sus contradicciones.